Protective Effect of Aqueous Leaves Antidote of Piper crocatum Against Lead Induced Oxidative Stress in Mice Liver - Lister, Inyoman E.; Zein, R.; Yerizal, E.; Fachrial, E.; Manjang, Y. (Asian Journal of Chemistry, 2016)
Present study investigated whether the Piper crocatum leaves antidote has given the protective effect against Pb(II) induced oxidative stress in mice liver. Oral administration of lead significantly increased serum hepatic markers (SGPT and SGOT), oxidative stress markers (malondialdehyde) and creatinine levels. Pre oral administration with Piper crocatum leaves antidote in lead intoxicated rats were significantly recovered the parameters. The histopathology analysis of liver section of experimental rats revealed that Piper crocatum leaves antidote exhibit the protective effect against lead(II) induced hepatic damage in mice.